Integration of amperometric electrochemical biosensor for detection of target nucleic acid in an automated sample preparation system - Ferhan Putra (2009)
This project focused on the preliminary development of a microfluidic flow-through module for an electrochemical deoxyribonucleic acid (DNA) sensor. The sensor shall replace a real-time polymerase chain reaction (RT-PCR) module currently integrated with a patented sample preparation kit developed at IBN suitable for point-of-care diagnosis. The development process involves three phases which includes a comparative study of different chip designs as well as fabrication techniques, an initial qualitative fluidics study followed by a quantitative characterization of the flow using actual reagents leading to a final optimization procedure and calibration. Through the first phase, it was observed that chips fabricated via photolithography yields better results than those fabricated via electron beam physical vapor deposition. Subsequent experimental results based on devices fabricated via photolithography presented herein have proven the promising operability of the flow system.